Improving Academic Supervision through Program Evaluation using the CIPP Model at Private High School in Bogor City - Tjoeng Sin Siong (Eduvest - Journal of Universal Studies, 2022)
This research wants to know how high the quality or condition in the implementation of academic supervision is, after the data collected is compared with certain criteria or standards. The research method is a scientific way to obtain data with certain goals and uses. Result of this research concluded that there is a match between the goals and objectives set in academic supervision. Graduates produced by private schools are increasingly able to compete with public schools to enter state universities.